Human rights centered global governance of quantum technologies: advancing information for all - UNESCO (2025)
Quantum technologies—encompassing quantum computing, communications, sensing, and materials—represent a groundbreaking frontier with the potential to revolutionize industries such as healthcare, energy, finance, and communications. However, like all transformative innovations, they come with opportunities, challenges and implications for human rights.